Literature Review : Socio-Economic Impact on Society due to the Covid-19 Pandemic - Anis Ansyori; Yuly Peristiowati (Journal Of Nursing Practice, 2023)
Background: Background the covid-19 pandemic has occurred since March 2020, the presence of the virus affects all aspects of life in society. Purpose: The purpose of this study is to determine the Socio-Economic Impact on Society due to the covid-19 pandemic.   Methods: The methodology used in this research is Literature Review LR. The results data used in this study were 10 journals sourced from 4 databases with the keywords pandemic, covid-19, socio-economic, society. Results: Based on journal reviews, it can be concluded that several articles show that the socio-economic impact on society due to the covid-19 pandemic is caused by several factors, including the health impact on the aspect of decreasing coverage of most health services, the economic slowdown causing an increase in unemployment, especially in the micro and industrial sector. households, in the social sector, increasing poverty, decreasing family income, decreasing food consumption, losing some types of work, for traders decreasing the number of sales. Conclusion: The study's findings indicate that the covid-19 pandemic has had adverse effects on various aspects of individuals' life institutions. These consequences encompass a drop in the accessibility of most healthcare services, a rise in unemployment in microbusinesses and home industries, an increase in poverty, a decrease in household income, a reduction in food consumption, and a decline in sales for businesses.